2003
DOI: 10.1136/heart.89.9.1032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of monophasic and biphasic shocks for transthoracic cardioversion of atrial fibrillation

Abstract: Objective: To compare the efficacy of cardioversion in patients with atrial fibrillation between monophasic damped sine waveform and rectilinear biphasic waveform shocks at a high initial energy level and with a conventional paddle position. Design: Prospective randomised study. Patients and setting: 227 patients admitted for cardioversion of atrial fibrillation to a tertiary referral centre. Results: 70% of 109 patients treated with an initial 200 J monophasic shock were cardioverted to sinus rhythm, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 14 publications
3
12
0
1
Order By: Relevance
“…1 In this sense the study's outcome is similar to that of the study reported by Page and colleagues, 2 who showed that for cardioversion of atrial fibrillation (AF), ''a biphasic shock waveform has greater efficacy, requires fewer shocks and lower delivered energy, and results in less dermal injury than a monophasic shock waveform''. Although a multicentre international study the number of patients recruited was less than that in Scholten's study population.…”
Section: Similar Efficacysupporting
confidence: 71%
See 1 more Smart Citation
“…1 In this sense the study's outcome is similar to that of the study reported by Page and colleagues, 2 who showed that for cardioversion of atrial fibrillation (AF), ''a biphasic shock waveform has greater efficacy, requires fewer shocks and lower delivered energy, and results in less dermal injury than a monophasic shock waveform''. Although a multicentre international study the number of patients recruited was less than that in Scholten's study population.…”
Section: Similar Efficacysupporting
confidence: 71%
“…1 However, there is evidence in this study and elsewhere to suggest that a biphasic defibrillation waveform is ''better'' than monophasic. [2][3][4][5] The sense that this should be so may be engendered by the past experience of electrophysiologists with ventricular defibrillators and the decrease in defibrillation threshold that was seen with the advent of biphasic shock waveforms in these devices.…”
mentioning
confidence: 53%
“…377 Cardioversion with monophasic waveforms should begin at 200 J and increase in stepwise fashion if not successful (Class IIa, LOE B). [372][373][374] Monomorphic VT (regular form and rate) with a pulse responds well to monophasic or biphasic waveform cardioversion (synchronized) shocks at initial energies of 100 J. If there is no response to the first shock, it may be reasonable to increase the dose in a stepwise fashion.…”
Section: Waveform and Energymentioning
confidence: 99%
“…[372][373][374][375][376] If the initial shock fails, providers should increase the dose in a stepwise fashion.…”
Section: Waveform and Energymentioning
confidence: 99%
“…[187][188][189][190][191] If the initial shock fails, providers should increase the dose in a stepwise fashion. Cardioversion of adult atrial flutter and other supraventricular tachycardias generally requires less energy; an initial energy of 50 J to 100 J is often sufficient.…”
Section: Supraventricular Tachycardias (Reentry Rhythms)mentioning
confidence: 99%